THE IMPACT OF ARTIFICIAL INTELLIGENCE ON CONSUMER BEHAVIOR AND MARKETING STRATEGIES IN THE DIGITAL ERA - Loso Judijanto; Henny Noviany; Deasy Sandya; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The influence and changes brought about by the implementation of Artificial Intelligence (AI) technologies on the way consumers behave, make purchase decisions and interact with brands, and how companies are responding to these changes by adapting their marketing strategies. This includes the use of AI for personalization of customer experiences, prediction of market trends, automation of interactions with consumers, and large-scale consumer data analysis, all of which aim to improve marketing effectiveness and create more meaningful relationships between brands and consumers in an ever-evolving digital environment. The research method in this study uses the literature method. The results show that it is important to strike a balance between technological innovation and ethical considerations in AI-based marketing. Therefore, companies that can effectively utilize AI while maintaining consumer trust will have a competitive advantage in the ever-evolving digital market.